A self-cleaning TiO2 coated mesh with robust underwater superoleophobicity for oil/water separation in a complex environment. Issue 69 (11th July 2016) - Dong, Zhe-Qin; Wang, Bao-Juan; Liu, Min; Ma, Xiao-hua; Xu, Zhen-Liang
Abstract : A TiO2 coated mesh with self-cleaning property, robust underwater superoleophobicity and high separation efficiency was fabricated by sol–gel method. Abstract : Porous materials with underwater superoleophobicity have recently become attractive candidates for oil/water separation, but are restricted in practical applications because of their easy contamination in air and poor resistance in a complex environment. Herein, we present a facile, efficient, and environmentally friendly approach to fabricating a TiO2 coated stainless mesh with both a photocatalytic self-cleaning property and excellent chemical resistance via a sol–gel method. The uniform, crack-free TiO2 nanoparticle coating layer endows the mesh with underwater superoleophobicity and corrosion resistance, which enables the effective separation of oil–water mixtures not only in a gentle environment but also in a complex environment such as acidic, alkaline and salty solutions. In addition, once these meshes were contaminated by organic molecules and lost their unique surface wettability, they could readily recover their origin wettability and separation performance by ultraviolet (UV) illumination owing to the photocatalysis of TiO2 . With respect to its exceptional stability, self-cleaning property and ease fabrication, the TiO2 coated mesh holds promising potential for practical oil/water separation applications.